The Role of Project method in EFL for Pre-intermediate Students - Mustafayev Ikram Ulash o’gli (Лучшие интеллектуальные исследования, 2024)
Abstract: This article highlights the significance of project-based learning in English education, exploring its positive impact on student engagement and overall language development. Based on research, project work demonstrates several benefits, including: increased Student Motivation: Project-based learning fosters a sense of purpose and ownership, motivating students to actively participate in the learning process. Integration of Language Skills: Projects seamlessly integrate all four language skills (reading, writing, speaking, and listening) and contribute to a holistic development of linguistic competence.